The Impact of ASCITIC Paracentesis on Symptomatic Outcomes in Palliative Patients: 3-Year Experience of a Melbourne Inpatient Palliative Care Unit Using Palliative Care Outcomes Collaboration Assessments - Kiran Iyer; Lucy Kernick (Gastroenterology Research and Practice)
Background. Ascites formation is a common occurrence in patients receiving palliative care. This is associated with symptoms that may respond to drainage. Aim. To review and quantify ascites-related symptoms pre- and post-paracentesis to evaluate its benefit in an inpatient palliative care setting. Methods. A retrospective audit of patients admitted to an inpatient palliative care unit who underwent paracentesis between November 2016 to June 2020 was performed. The primary outcome was a symptomatic benefit of paracentesis. Secondary outcomes assessed the associated complications as well as the alterations to functional status. Data were analysed using a paired T-test. Results. 43 instances of ascitic paracentesis were performed on a total of 26 patients. Three patients were excluded from the study due to the technical failure of their paracentesis procedure. There was a mean 0.16-point reduction in pain (95% confidence interval (CI) −0.33 to 0.65), a mean 0.03-point increase in dyspnoea (95% CI −0.51 to 0.46), and a mean 0.32-point reduction in nausea (95% CI −0.09 to 0.74). Conclusions. Ascitic paracentesis in the palliative setting may demonstrate some benefit in managing symptoms associated with ascites. Although the findings of this study did not achieve statistical significance, these results may be substantiated by future studies with larger sample size.